2008
DOI: 10.1128/iai.00136-08
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae Infection and Environmental Tobacco Smoke Inhibit Lung Glutathione Adaptive Responses and Increase Oxidative Stress

Abstract: Chronic cigarette smoking evokes a lung glutathione (GSH) adaptive response that results in elevated GSH levels in the lung epithelial lining fluid (ELF). Currently, little is known about how the lung regulates or maintains steady-state levels of ELF GSH. Pathogens such as Mycoplasma pneumoniae can exacerbate airway inflammation and oxidative stress. The present study examined whether M. pneumoniae infections synergize with environmental tobacco smoke (ETS) to disrupt lung GSH adaptive responses. Mice were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 52 publications
4
36
0
Order By: Relevance
“…After 24 hours exposure, we observed that CSE, even at a 5% concentration, was ineffective on GSH intracellular levels. This result is well in agreement with the findings of Pace et al showing that total intracellular glutathione is not affected after a 18 hours treatment [20], and has been observed also in other epithelial airway cells [14,47,48], even if not in all cell types [35,49,50]. It could be explained as a cell adaptive response to a chronic CSE exposure.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 82%
“…After 24 hours exposure, we observed that CSE, even at a 5% concentration, was ineffective on GSH intracellular levels. This result is well in agreement with the findings of Pace et al showing that total intracellular glutathione is not affected after a 18 hours treatment [20], and has been observed also in other epithelial airway cells [14,47,48], even if not in all cell types [35,49,50]. It could be explained as a cell adaptive response to a chronic CSE exposure.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 82%
“…Cells were plated at a density of 2.0 ϫ 10 5 cells/well on 24-well tissue culture plates (Corning) and allowed to adhere overnight. Viability was determined from lactate dehydrogenase release into the medium 24 h after the beginning of exposure as described previously (24).…”
Section: Sources Of Purified Thioredoxin Reductase and Glutathionementioning
confidence: 99%
“…Skin GSH levels were determined according to the protocol described previously (Kariya et al, 2008). In brief, skin tissues were weighed, sonicated on ice in KPBS buffer (50 mM potassium phosphate buffer, 17.5 mM EDTA, 50 mM serine, and 50 mM boric acid, pH 7.4), and incubated in the dark at room temperature for 30 min in the presence of monobromobimane (3 mM in acetonitrile).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was stopped by the addition of 70% perchloric acid. The samples were then centrifuged at 16,000g at 4°C for 10 min, and the supernatant was removed, transferred to a high-performance liquid chromatography vial, and analyzed for GSH on a Hitachi high-pressure liquid chromatograph (model L-2420; San Jose, CA) equipped with a fluorometric detector (model L-2480) as previously described with minor modifications, using excitation and emission wavelengths at 390 and 480 nm, respectively (Kariya et al, 2008).…”
Section: Methodsmentioning
confidence: 99%